Near‐surface mean wind in Switzerland: Climatology, climate model evaluation and future scenarios. (13th May 2019) - Graf, Michael; Scherrer, Simon C.; Schwierz, Cornelia; Begert, Michael; Martius, Olivia; Raible, Christoph C.; Brönnimann, Stefan
Abstract: Near‐surface seasonal and annual mean wind speed in Switzerland is investigated using homogenized observations, Twentieth Century Reanalysis (20CRv2c) data and raw model output of a 75 member EURO‐ CO o R dinated D ownscaling EX periment regional climate model (RCM) ensemble for present day and future scenarios. The wind speed observations show a significant decrease in the Alps and on the southern Alpine slopes in the period 1981–2010. However, the 20CRv2c data reveal that the recent trends lie well within the decadal variability over longer time periods and no clear signs of a systematic wind stilling can be found for Switzerland. The ensemble of RCMs shows large biases in the annual mean wind speed over the Jura mountains, and some members also show large biases in the Alps compared to station observations. The spatial distribution of the model biases varies strongly between the RCMs, while the resolution and the driving global model have less impact on the pattern of the model bias. The RCMs are mostly able to represent the seasonality of wind speed on the Plateau but miss important details in complex terrain related to local wind systems. Most models show no significant changes in near‐surface mean wind speed until the end of the 21st century. The model ensemble changes range from a 7% decrease to a 6% increase with an ensemble mean decrease of 1 to 2%. Due to model biases, the scale mismatch between model grid and station observations and the missing representation of local winds in the simulations, the changes need to be interpreted with utmost care. Future assessments might lead to major revisions even for the sign of the projected changes, in particular over complex terrain. Abstract : Recent declines of mean wind speed in the Swiss Alps lie well within the long‐term variability. Current regional climate model simulations with 12‐ to 50‐km grid resolution are mostly able to represent the seasonality of wind speed on the Swiss Plateau but miss important details in the Alps. No significant changes in mean wind speed are projected until the end of the 21st century, but major revisions of the results are possible with higher resolution simulations, in particular over complex terrain.